A Rare Site of Metachronous Metastases from Renal Cell Carcinoma (Journal of Kidney Cancer, 2024)
Secondary metastatic involvement of the testis is a rare occurrence, particularly in cases of metastasis from renal cell carcinoma (RCC). We present a case of metachronous contralateral testicular metastasis from RCC in a 55-year-old man, occurring 2 years after radical nephrectomy. Following a thorough evaluation that ruled out systemic disease, the patient underwent a Chevassu procedure and right inguinal orchidectomy. Histopathological analysis confirmed metastatic involvement of the right testis by RCC. Metastasis to the testis from RCC is uncommon, with only a few cases reported in the literature. Isolated metachronous metastasis without systemic involvement is even rarer. This case highlights the importance of considering testicular metastasis in patients with a history of RCC, emphasizing the need for comprehensive evaluation and surgical resection when feasible, as it has been associated with prolonged survival.